2018
DOI: 10.1108/jima-09-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Implementing air cargo halal warehouse: insight from Malaysia

Abstract: Purpose This study aims to discuss the challenges in implementing halal warehouse in the air cargo context along with the standard handling process for the storage of halal product for import and export purposes. This is vital to ensure that halal products do not get contaminated and should comply to halal logistics standard throughout the supply chain process. Design/methodology/approach This exploratory study adopts single case study to better understand the definition of halal warehouse, the challenges in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…This study found that LSP's attraction to offers CLSC is generated from positive income due to the lower number of providers and level of competition (Tan & Li, 2018), derived from the e-commerce phenomenon were forcing the traditional retailers to closed down their stores and that vacant location is replaced with the F&B retailers (Zhang et al, 2016), changes in consumer's habits like increasing for the consumption of frozen food and ready to-eat-meal which sees the used for more CLSC to delivers these products to retail stores (Al Theeb et al, 2020;Khan & Ali, 2021), demand from customers, organisation readiness, and government regulation. In the future, it is expected that the demand will increase mainly derived from the halal and pharmaceutical sectors (Abideen & Mohamad, 2020;Abideen & Mohamad, 2019;Khan et al, 2019;Rahman et al, 2018). For the time being, the market competition is modest as the LSPs need to be ready for their capital investments, ability to invest in cold chain assets and related certifications for increasing the competitiveness level which seems too high for smaller companies.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study found that LSP's attraction to offers CLSC is generated from positive income due to the lower number of providers and level of competition (Tan & Li, 2018), derived from the e-commerce phenomenon were forcing the traditional retailers to closed down their stores and that vacant location is replaced with the F&B retailers (Zhang et al, 2016), changes in consumer's habits like increasing for the consumption of frozen food and ready to-eat-meal which sees the used for more CLSC to delivers these products to retail stores (Al Theeb et al, 2020;Khan & Ali, 2021), demand from customers, organisation readiness, and government regulation. In the future, it is expected that the demand will increase mainly derived from the halal and pharmaceutical sectors (Abideen & Mohamad, 2020;Abideen & Mohamad, 2019;Khan et al, 2019;Rahman et al, 2018). For the time being, the market competition is modest as the LSPs need to be ready for their capital investments, ability to invest in cold chain assets and related certifications for increasing the competitiveness level which seems too high for smaller companies.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…According to Tieman & Ghazali (2014), to maintain the Halal assurance for Halal products, utilising a controlled temperature is one of the characteristics of a Halal Supply Chain foundation. Halal supply chain requires the availability and use of appropriate logistics infrastructures such as warehouse, storage, transport, retail, and cold chain facilities (Khan et al, 2019;Rahman et al, 2018). The same issue has been raised by Abu et al (2018), where the temperature breakdowns during halal meat handling are being questioned.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…The Competitiveness of Indonesian Halal Food … https://journal.walisongo.ac.id/index.php/economica | 31 used by companies to maintain and maintain product halalness (Hameeda et al 2016). Halal integrity is the keyword in the halal value chain (Abdul Rahman et al 2018). The following is an example of a halal supply chain image to be able to maintain product halalness.…”
Section: Halal Value Chain Conceptmentioning
confidence: 99%